The importance of being open: publishing OA monographs - Watson, D; Boehmer, E; Leach, EE; Morrison, C; Barnes, L; Redman, A; Sterkens, A; Wickham, C (Bodleian Libraries, University of Oxford, 2023)
Long form research, including monographs, is starting to feature in research funder policy mandates. UK Research and Innovation have recently announced a monographs component to their open access policy, starting from 2024. This developing form of publication has many exciting advantages in making research openly available, but also comes with its own set of challenges. This session will explore Open Monograph publishing primarily from a researcher’s point of view, and the alternative approaches and new models that are being developed. Chaired by Professor Chris Wickham, you will hear from a range of speakers who have published OA monographs or are involved in supporting the transition to them. This session will: Give an overview of the current situation with OA for long form research.